Analysis of hollow steel piles subjected to buried blast loading. (September 2016) - Chakraborty, Tanusree
Abstract: Dynamic analyses of hollow steel end bearing piles in sandy soil subjected to buried blast loading are performed herein using the three-dimensional nonlinear finite element method and the coupled Eulerian–Lagrangian technique. Parametric sensitivity studies are performed for different axial load magnitudes on the pile head, elastic moduli, mass densities, different friction angles of soil and Poisson's ratio. The lateral deflection of the pile head decreases with increasing axial load. The peak particle velocity in soil increases with a decrease in elastic modulus, mass density and friction angle of soil and increases significantly if the soil is incompressible.